“A mão pesada da morte acaba de arrebatar mais uma vida preciosa: sensibilidades nos anúncios de falecimento no jornal “O Piauhy” entre 1869 e 1873 (Ágora Journal, 2020)
As part of almost infinite possibilities of themes to be investigated by the field of cultural history, this work presents the sensitivities conveyed by the inhabitants of Piauí (Brazil) when announcing the death of their loved ones in the newspaper “O Piauhy” between 1869 and 1873. It also aims to demonstrate that the obituaries provide several clues that can portray the social configuration and the political relations established in a given place and time, which make them a fruitful source of historical analysis.